2022
DOI: 10.35790/ecl.v10i2.38288
|View full text |Cite
|
Sign up to set email alerts
|

Role of Troponin Test in Diagnosis and Management of Acute Myocardial Infarction

Abstract: To date, AMI is still an important global health problem because of relatively high morbidity and mortality rates. Diagnosis of AMI can be established if there are at least two of the three criteria to be met, namely chest pain (anamnesis), persistent changes in electrocardiographic (ECG), as well as cardiac biomarker creatine myocardial band (CK-MB), cardiac troponin T (cTnT), or cardiac troponin I (cTnI). Treatment for AMI patients consists of reperfusion therapy and pharmacological therapy. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…December 2013, it was found that the majority of patients were men with a total of 43 people (86%). 13,16 The most common location of infarction in the study was inferior with 20 people (29.9%) followed by inferoposterior infarction locations (25.4%). [17][18][19] The hsTnI levels in this study had a median of 6,519 ng/L.…”
Section: Resultsmentioning
confidence: 82%
“…December 2013, it was found that the majority of patients were men with a total of 43 people (86%). 13,16 The most common location of infarction in the study was inferior with 20 people (29.9%) followed by inferoposterior infarction locations (25.4%). [17][18][19] The hsTnI levels in this study had a median of 6,519 ng/L.…”
Section: Resultsmentioning
confidence: 82%